Mice lacking adenosine 2A receptor reveal increased severity of MCD-induced NASH. Issue 3 (December 2019) - Zhou, Jing; Li, Honggui; Cai, Yuli; Ma, Linqiang; Matthews, Destiny; Lu, Bangchao; Zhu, Bilian; Chen, Yanming; Qian, Xiaoxian; Xiao, Xiaoqiu; Li, Qifu; Guo, Shaodong; et al.
Abstract : Adenosine 2A receptor (A2A R) exerts a protective role in obesity-related non-alcoholic fatty liver disease. Here, we examined whether A2A R protects against non-alcoholic steatohepatitis (NASH). In C57BL/6J mice, feeding a methionine- and choline-deficient diet (MCD) resulted in significant weight loss, overt hepatic steatosis, and massive aggregation of macrophages in the liver compared with mice fed a chow diet. MCD feeding also significantly increased the numbers of A2A R-positive macrophages/Kupffer cells in liver sections although decreasing A2A R amount in liver lysates compared with chow diet feeding. Next, MCD-induced NASH phenotype was examined in A2A R-disrupted mice and control mice. Upon MCD feeding, A2A R-disruptd mice and control mice displayed comparable decreases in body weight and fat mass. However, MCD-fed A2A R-disrupted mice revealed greater liver weight and increased severity of hepatic steatosis compared with MCD-fed control mice. Moreover, A2A R-disupted mice displayed increased severity of MCD-induced liver inflammation, indicated by massive aggregation of macrophages and increased phosphorylation states of Jun-N terminal kinase (JNK) p46 and nuclear factor kappa B (NFκB) p65 and mRNA levels of tumor necrosis factor alpha, interleukin-1 beta, and interleukin-6. In vitro, incubation with MCD-mimicking media increased lipopolysaccharide (LPS)-induced phosphorylation states of JNK p46 and/or NFκB p65 and cytokine mRNAs in control macrophages and RAW264.7 cells, but not primary hepatocytes. Additionally, MCD-mimicking media significantly increased lipopolysaccharide-induced phosphorylation states of p38 and NFκB p65 in A2A R-deficient macrophages, but insignificantly decreased lipopolysaccharide-induced phosphorylation states of JNK p46 and NFκB p65 in A2A R-deficient hepatocytes. Collectively, these results suggest that A2A R disruption exacerbates MCD-induced NASH, which is attributable to, in large part, increased inflammatory responses in macrophages.